Resilience as Regulation of Developmental and Family Processes. Issue 1 (February 2015) - MacPhee, David; Lunkenheimer, Erika; Riggs, Nathaniel
<x xml:space="preserve">Abstract</x> Resilience can be defined as establishing equilibrium subsequent to disturbances to a system caused by significant adversity. When families experience adversity or transitions, multiple regulatory processes may be involved in establishing equilibrium, including adaptability, regulation of negative affect, and effective problem‐solving skills. The authors' resilience‐as‐regulation perspective integrates insights about the regulation of individual development with processes that regulate family systems. This middle‐range theory of family resilience focuses on regulatory processes across levels that are involved in adaptation: whole‐family systems such as routines and sense of coherence; coregulation of dyads involving emotion regulation, structuring, and reciprocal influences between social partners; and individual self‐regulation. Insights about resilience‐as‐regulation are then applied to family‐strengthening interventions that are designed to promote adaptation to adversity. Unresolved issues are discussed in relation to resilience‐as‐regulation in families, in particular how risk exposure is assessed, interrelations among family regulatory mechanisms, and how families scaffold the development of children's resilience.